P200 Preliminary Evaluation Of The Fungal Airway Microbiome In Adult Cystic Fibrosis By Next-generation Sequencing, Culture And Staining Techniques. (10th November 2014) - Felton, IC; Benson, S; Nicholson, A; Al-Shafi, K; James, P; Cox, MJ; Walley, AJ; Moffatt, MF; Bilton, D; Loebinger, MR; Simmonds, NJ; Cookson, WO
Abstract : Introduction: The prevalence and diversity of fungal airway isolates is increasing in cystic fibrosis (CF). Amidst an extending spectrum of fungal complications, lack of standardised mycology methods and poor sensitivity of culture-dependent techniques renders interpretation of isolates challenging. Aims: To evaluate the diagnostic utility of fungal cytology and microbiology stains in addition to prolonged sputum culture from adult CF patients in comparison to standard mycology techniques. Secondly, to develop a novel, next-generation sequencing assay targeting the ITS2 region of the fungal ribosomal-RNA gene to comprehensively profile the sputum fungal microbiota. Methods: Sputum samples were investigated by a panel of three mycology techniques: prolonged fungal culture (each examined at: Day7, D14, D21, D28); Calcofluor White (CFW) stain; Grocott's Methenamine Silver (GMS) stain. A cohort of samples was also subject to broad-spectrum fungal next-generation sequencing. Results: 25 adult patients provided 45 sputum samples. Four fungal species were cultivatable: Candida species (26.6%); Aspergillus fumigatus (4.4%); Scedosporium apiospermum (15.5%) and Exophiala dermatitidis (11.1%). Prolonged culture significantly increased overall fungal prevalence by 22% compared to standard duration (D7) p = 0.008 ) . A significant increase of 11.1% in S. apiopspermum prevalence was observed p = 0.02 ), whilst all E. dermatitidis isolates required prolonged culture. The sensitivity of GMS and CFW stains (85% and 93%) compared favourably to standard duration culture (29%). DNA extracted from a pilot group of these sputum samples (n = 14/45) was subject to PCR using barcode-indexed ITS2 primers designed for Illumina-MiSeq amplicon sequencing. Fungal taxa were detected in all samples, of which seven samples (50%) were negative after prolonged culture. Preliminary sequencing analysis of an extended sample cohort (n = 30) has detected 89 fungal taxa, from which only four species were cultured. Conclusions: Prolonged fungal culture is associated with a significant increase in fungal prevalence. The increased sensitivity is restricted to less common filamentous fungi associated with increasing pathogenicity: S. apiospermum and E. dermatitidis. The predictive value of stains in identifying samples positive at prolonged culture, but negative at standard duration illustrates their clinical utility. Illumina-MiSeq ITS2-amplicon sequencing directly from sputum has identified a more diverse CF airways fungal microbiota. Preliminary analysis suggests that this is a highly sensitive tool for detecting fungi from sputum, including species which are refractory to standard and enhanced culture.